Thermophilic bio-electro carbon dioxide recycling harnessing renewable energy surplus. (February 2021) - Rovira-Alsina, Laura; Balaguer, M. Dolors; Puig, Sebastià
Graphical abstract: Highlights: Renewable energy surplus can be valorized through microbial electrosynthesis. Intermittent power supply conditions may boost the product per energy ratio. Enriched thermophilic microbiomes can be highly resilient to fluctuating conditions. (Bio)electrochemical processes co-exist with fermentative reactions. Abstract: Renewable energies will represent an increasing share of the electricity supply, while flue and gasification-derived gases can be a promising CO2 feedstock with a heat load. In this study, microbial electrosynthesis of organic compounds from CO2 at high temperature was proposed as an alternative for valorising energy surplus and decarbonizing the economy. The unremitting fluctuation of renewable energy sources was assessed using two bioreactors at 50 °C, under circumstances of continuous and intermittent power supply (ON-OFF; 8–16 h), simulating an off-grid photovoltaic system. Results highlighted that maximum acetate production rate (43.27 g m −2 d −1 ) and columbic efficiency (98%) were achieved by working with an intermittent energy supply, while current density was reduced three times. This boosted the production of acetate per unit of electricity provided up to 138 g kWh −1 and reinforced the robustness of the technology by showing resilience to tolerate perturbations and returning to its initial state.